Bone turnover biomarkers identify unique prognostic risk groups in men with castration resistant prostate cancer and skeletal metastases: Results from SWOG S0421. (2018) - Lara Jr., P.N.; Plets, M.; Tangen, C.; Gertz, E.; Vogelzang, N.J.; Hussain, M.; Twardowski, P.W.; Garzotto, M.G.; Monk, J.P.; Carducci, M.; Goldkorn, A.; Mack, P.C.; et al.
Abstract: Background: Skeletal metastases often occur in men with castration-resistant prostate cancer (CRPC) where bone biomarkers are prognostic for overall survival (OS). In those with highly elevated markers, there is preferential benefit from bone-targeted therapy. In the phase IIIS0421 docetaxel +/− atrasentan trial, clinical covariates and bone biomarkers were analyzed to identify CRPC subsets with differential outcomes. Subjects and methods: Markers of bone resorption [N-telopeptide-NTx; pyridinoline-PYD] and formation [C-terminal collagen propeptide-CICP; bone alkaline phosphatase-BAP] were measured in pre-treatment sera. Bone biomarkers and clinical covariates were included in a Cox model for OS; bone markers were added in a stepwise selection process. Receiver operating characteristic (ROC) curves were constructed for risk factor models +/− bone markers. Significant variables were allowed to compete in a classification and regression tree (CART) analysis. Hazard ratios(HR) were calculated by comparing OS in each of the terminal nodes to a reference group in a Cox model. Results: 750 patients were included. Each bone marker significantly contributed to the risk factor-adjusted OS Cox model, with higher levels associated with worse OS. BAP (HR = 1.15, p  = 0.008), CICP (HR = 1.27, p  < 0.001), and PYD (HR = 1.21, p  = 0.047) in combination were significantly associated with OS. Prognostic accuracy was improved by addition of bone markers to clinical covariates. CART analysis selected CICP, BAP, hemoglobin, and pain score for the final OS model, identifying five prognostic groups. Conclusions: Elevated serum bone biomarker levels are associated with worse OS in bone-metastatic CRPC. Bone biomarkers can identify unique prognostic subgroups. These results further define the role of bone biomarkers in the design of CRPC trials.